Moderate increase of precipitation stimulates CO2 production by regulating soil organic carbon in a saltmarsh - Zhang, Lirong; Han, Guangxuan; Zhou, Lifeng; Li, Xinge; Wang, Xiaojie; Zhang, Xiaoshuai; Xiao, Leilei (Frontiers in Microbiology, 2024)
Saltmarsh is widely recognized as a blue carbon ecosystem with great carbon storage potential. Yet soil respiration with a major contributor of atmospheric CO2 can offset its carbon sink function. Up to date, mechanisms ruling CO2 emissions from saltmarsh soil remain unclear. In particular, the effect of precipitation on soil CO2 emissions is unclear in coastal wetlands, due the lack of outdoor data in real situations. We conducted a 7-year field manipulation experiment in a saltmarsh in the Yellow River Delta, China. Soil respiration in five treatments (−60%, −40%, +0%, +40%, and + 60% of precipitation) was measured in the field. Topsoils from the last 3 years (2019–2021) were analyzed for CO2 production potential by microcosm experiments. Furthermore, quality and quantity of soil organic carbon and microbial function were tested. Results show that only the moderate precipitation rise of +40% induced a 66.2% increase of CO2 production potential for the microcosm experiments, whereas other data showed a weak impact. Consistently, soil respiration was also found to be strongest at +40%. The CO2 production potential is positively correlated with soil organic carbon, including carbon quantity and quality. But microbial diversity did not show any positive response to precipitation sizes. r-/K-strategy seemed to be a plausible explanation for biological factors. Overall, our finding reveal that a moderate precipitation increase, not decrease or a robust increase, in a saltmarsh is likely to improve soil organic carbon quality and quantity, and bacterial oligotroph:copiotroph ratio, ultimately leading to an enhanced CO2 production.